2013
DOI: 10.1186/1472-698x-13-31
|View full text |Cite
|
Sign up to set email alerts
|

Illegal yet developmentally normative: a descriptive analysis of young, urban adolescents’ dating and sexual behaviour in Cape Town, South Africa

Abstract: BackgroundIn South Africa, it is illegal for adolescents under age 16 years to engage in any sexual behaviour whether kissing, petting, or penetrative sex, regardless of consent. This cross-sectional study investigated the extent to which young adolescents engage in various sexual behaviours and the associations between dating status and sexual behaviours.MethodGrade 8 adolescents (N = 474, ages 12–15 years, mean = 14.14 years) recruited from Cape Town schools completed surveys providing information about thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 40 publications
0
46
0
Order By: Relevance
“…only1[57]2[69,78]3Regional lang. & English17[40,41,43,44,4749,53,54,56,5962,7375]7[40,41,70,76,77,79,80]22 b  Not stated11[42,45,5052,55,58,6366]5[46,67,68,71,72]16AI – anal intercourse, VI – vaginal intercourse, UAI – unprotected anal intercourse, UVI – unprotected vaginal intercourse, F – female, M – male, Mix – data available on mixed gender only, FSW – female sex worker, MSM – men who have sex with men, shebeen – an informal establishment serving alcohol, STI – sexually transmitted infection, VCT – voluntary counselling and testing, ACASI – audio computer-assisted self-interview, FTFI – face-to-face interview, SAQ – self-administered questionnaire, CRS – cluster random sample, SRS – simple random sample, RDS – respondent-driven sample, RCT – randomized controlled trial a Studies which reported AI prevalence for unprotected AI only. b Sum lower than expected as two studies report on both higher and general-risk populations. c Recall period referred to here as “general” when participants were asked “Do you practise anal sex”, or similar. d Defined by author as “high risk” but no definition provided; sample consists of 79% FSW [70]. …”
Section: Resultsmentioning
confidence: 99%
“…only1[57]2[69,78]3Regional lang. & English17[40,41,43,44,4749,53,54,56,5962,7375]7[40,41,70,76,77,79,80]22 b  Not stated11[42,45,5052,55,58,6366]5[46,67,68,71,72]16AI – anal intercourse, VI – vaginal intercourse, UAI – unprotected anal intercourse, UVI – unprotected vaginal intercourse, F – female, M – male, Mix – data available on mixed gender only, FSW – female sex worker, MSM – men who have sex with men, shebeen – an informal establishment serving alcohol, STI – sexually transmitted infection, VCT – voluntary counselling and testing, ACASI – audio computer-assisted self-interview, FTFI – face-to-face interview, SAQ – self-administered questionnaire, CRS – cluster random sample, SRS – simple random sample, RDS – respondent-driven sample, RCT – randomized controlled trial a Studies which reported AI prevalence for unprotected AI only. b Sum lower than expected as two studies report on both higher and general-risk populations. c Recall period referred to here as “general” when participants were asked “Do you practise anal sex”, or similar. d Defined by author as “high risk” but no definition provided; sample consists of 79% FSW [70]. …”
Section: Resultsmentioning
confidence: 99%
“…[11] Sensitivity to personal circumstances also indicates cognisance that consensual sexual exploration among adolescents is developmentally normative. [4] Age difference was one of several factors considered by social workers in this study when deciding whether to report consensual underage sex. This is contrary to the approach in the recently amended Act [13] which makes age difference the sole factor guiding whether the behaviour will attract criminal sanction.…”
Section: Discussionmentioning
confidence: 90%
“…[4] Sections 15 and 16 of the Criminal Law [Sexual Offences and Related Matters] Amendment Act [1] (hereafter the 'Sexual Offences Act'), which criminalised underage consensual sex and sexual activity have been extensively criticised. Commentators contended that criminalising consensual underage sex is incongruent with developmentally normative sexual practices among adolescents, [4][5] is incompatible with other legislation like the Children's Act and the Choice of Termination of Pregnancy Act, [6][7] contrary to the principle of 'the best interests of the child' and inconsistent with children's constitutional rights to bodily and psychological integrity and privacy. [6] A further criticism of the Sexual Offences Act was that it made it incumbent on all service providers, including doctors, social workers, psychologists and others to report consensual underage sex to a police official.…”
mentioning
confidence: 99%
“…An abundance of literature suggests that adolescent who use drug and alcohol are significantly prone to have sex at earlier ages (Lammers et al, 1999;Lohman & Billings, 2008;Rosenbaum & Kandel, 1990). Adolescents who are involved in school problems also have an earlier age of first sex (Gevers, Matthews, Cupp, Russell, & Jewkes, 2013;Lohman & Billings, 2008).…”
Section: Adolescent Delinquencymentioning
confidence: 99%